2018
DOI: 10.1021/acs.jmedchem.8b00346
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Pyrimido[4,5-d]pyrimidine-2,4(1H,3H)-diones as Potent and Selective Epidermal Growth Factor Receptor (EGFR) Inhibitors against L858R/T790M Resistance Mutation

Abstract: First-generation epidermal growth factor receptor (EGFR) inhibitors, gefitinib and erlotinib, have achieved initially marked clinical efficacy for nonsmall cell lung cancer (NSCLC) patients with EGFR activating mutations. However, their clinical benefit was limited by the emergence of acquired resistance mutations. In most cases (approximately 60%), the resistance was caused by the secondary EGFR T790M gatekeeper mutation. Thus, it is still desirable to develop novel third-generation EGFR inhibitors to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The crystal structure of EGFR (3W2S) is selected for the docking study due to its high resolution (1.9 Å), ability to form important water‐mediated interactions with the ligand and amino acid Thr 790 residue, as well as its ability to form essential hydrogen bonds with amino acids like Met 793. [ 51,63,64 ] Several interactions such as hydrogen bond, hydrophobic interactions, π interaction, and so forth, with the active pocket of the targeted enzyme, were considered for the docking score of the synthesized compounds. The docking score, binding energies, and types of interactions of all the synthesized compounds are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of EGFR (3W2S) is selected for the docking study due to its high resolution (1.9 Å), ability to form important water‐mediated interactions with the ligand and amino acid Thr 790 residue, as well as its ability to form essential hydrogen bonds with amino acids like Met 793. [ 51,63,64 ] Several interactions such as hydrogen bond, hydrophobic interactions, π interaction, and so forth, with the active pocket of the targeted enzyme, were considered for the docking score of the synthesized compounds. The docking score, binding energies, and types of interactions of all the synthesized compounds are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported a novel series of pteridin‐7(8H)‐one‐based irreversible inhibitors 16 targeting EGFR kinase by scaffold hopping using SHAFTS . Hao et al discovered two series of potent and selective EGFR inhibitors againstL858R/T790 M resistance mutation by scaffold hopping with SHAFTS . Li et al discovered and designed a series of novel and potent DPP‐4 inhibitors for treating type 2 diabetes mellitus (T2DM) based on a natural product lead using SHAFTS .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…The compounds were investigated against EGFR WT and EGFR L858R/T790M , and the results indicated that they were more selective to the mutant form. When compared using the reference AZD9291, the time of onset and duration of action were similar to 284 , but in the A431 xenograft model, 286 showed less inhibition in tumor growth ( Hao et al, 2018 ).…”
Section: Fused Pyrimidine Derivativesmentioning
confidence: 93%
“… 2) At R 1 : the presence of pyrrolidine helps in improving the solubility and pharmacokinetics of the compounds ( Xu et al, 2013 ). Substitution with N -propenone makes the compound selective against double mutant EGFR ( Hao et al, 2018 ). 3) At R 2 : the short alkyl chain of two to three carbons was investigated.…”
Section: Fused Pyrimidine Derivativesmentioning
confidence: 99%